Fluctuating asymmetry in genetically improved Nile tilapia (Oreochromis Niloticus) strains - Muallil, Richard N.
Genetically Improved Nile Tilapias (GINTs) are developed through selective breeding to improve performance traits e.g. growth. GINTs boosted dramatically tilapia production in the Philippines in the last decade. To sustain tilapia production in the Philippines, the general health of GINTs should be continuously monitored. Fluctuating asymmetry (FA) level based on 13 bilateral characters was compared among three (GenoMar Supreme Tilapia, GIFT and FaST) of the widely used GINT strains in the country. FA is hypothesized to increase with stress and may be associated with some measures of fitness, such as mortality and susceptibility to infections. Composite FA (CFA) level based on the summed FA values across all the characters did not differ significantly among strains. However, when each character was assessed separately, FA level for poercular length was significantly higher in GenoMar Supreme Tilapia strain than the other two strains. For gill rakers, FA level was significantly higher in GenoMar Supreme Tilapia strain than FaST strain only. FA level FaST and GIFT strains did not differ significantly for all characters. Weak FA variation among strains in some characters may act as random noise resulting in a failure of CFA analyses in detecting significant FA variations among the strains. Given the direct relationship between stress and FA, this study suggest that stress level, which could be genetic or/and environmental in origin, measured as FA is highest in GenoMar Supreme Tilapia strain relative to GIFT and FaST strains
Computer print out.
Keywords: Nile tilapia -- Philippines